Professional Mobility and Institutional Cooperation in Kazakhstan: A Model for Dynamic Library Services in Asia - Alenzuela, Reysa C. (Nazarbayev University, 2017)
Globalization is an impetus for broader collaboration and academic mobility. The need for global competitiveness in terms of knowledge and services gave rise to various forms of cooperation from the institutional level to the subsystems like the library. Libraries as key players in building a culture of research and knowledge development need to meet the international standards. This empirical descriptive-narrative shares about the role of institutional cooperation and professional mobility in order for libraries to develop dynamic services and build on the capacity of local practitioners. Insights from vicarious experience as a librarian and internationally patterned services will also be discussed. This hopes to provide a model for developing libraries in Asia.
Keywords: academic mobility; institutional cooperation; cross-border collaboration; ibrary services; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science